Critical Examination of the School Environment in Terms of Augmenting Motivation Among Students in Junior High Schools in Palu - Putri, Aulia; Mashuri, Saepudin; Kahar, M Iksan; Salahudin, Salahudin; Dulumina, Gunawan B (Paedagogia: Jurnal Pendidikan, 2025)
This study aims to determine whether there is an influence of the school environment on the learning motivation of students at Negeri 9 Palu. The research method used in this study is quantitative. The instrument in this study uses a questionnaire. The research data that has been collected is analyzed with the help of a computer program using statistical product and service solution (SPSS), and the results of the hypothesis test are analyzed using a simple linear regression test. The results of the study show a calculated t value of 7.727> t table 1.986. With a significant value of 0.001 < 0.005. The results of this study can also be seen in the coefficient of determination that the contribution of the influence of the variable (X), namely the school environment, to the variable (Y), namely learning motivation, is 41%. The conclusion of the results of this study shows that there is a significant influence of the school environment on the learning motivation of students in the subject of Islamic Religious Education at SMP Negeri 9 Palu. This finding emphasizes the importance of a supportive and engaging school environment in fostering students' motivation to learn, particularly in subjects like Islamic Religious Education. Future research could explore additional factors that may further enhance learning motivation in this context.